Tshwane, Pretoria, Phelindaba : structure - agency interaction and the transformation of a South African region up to 1994, with prospects for the immediate future - Hattingh, P.S. (University of Pretoria, 2014)
Thesis (DPhil)--University of Pretoria, 1998.